Computation of flow features and hydrodynamic coefficients around heave plates oscillating near a seabed. (November 2015) - Garrido-Mendoza, Carlos A.; Thiagarajan, Krish P.; Souto-Iglesias, Antonio; Colagrossi, Andrea; Bouscasse, Benjamin
Abstract: For the past few years, heave plates have been used in the offshore industry due to their favorable hydrodynamic characteristics in oscillating flows, i.e., increased added mass and damping. The hydrodynamic coefficients of heave plates are strongly influenced by the proximity of solid boundaries. Assessing how this variation depends on the proximity to the seabed and on the amplitude of the oscillation is the main aim of this paper. In this process, a new model describing the work done by damping in terms of the flow enstrophy is described herein. This new approach is able to provide a direct correlation between the vortex shedding processes and the linear damping coefficient. Numerical simulations have been performed using the finite volume open source solver OpenFOAM. Simulations have been conducted on a solid circular disc oscillating axially in water at various elevations above an impermeable seabed boundary. Results for hydrodynamic coefficients are validated against previously published experimental data. At low KC numbers, a systematic increase in added mass and damping, corresponding to an increase in the seabed proximity, is observed. As seen in experiments, a critical KC where the monotonic trend of the hydrodynamic coefficients with KC is disrupted and that depends on the seabed distance exists. The physical behavior of the flow around the critical KC is explained through an analysis of the flow enstrophy. Abstract : Highlights: Numerical simulations on a heave plate oscillating near seabed conducted. Added mass and damping have been found to increase with the proximity to the seabed. Depth dependent critical KC found, above which A33 deviates from a linear trend. Alternative way to obtain the damping looking at the dissipation mechanisms devised. Damping obtained from enstrophy integral and classical damping formulation discussed.